2005
DOI: 10.1007/s11211-005-3369-1
|View full text |Cite
|
Sign up to set email alerts
|

Belief in a Just World, Causal Attributions, and Adjustment to Sexual Violence

Abstract: What influence do the personal belief in a just world (i.e., the perception that one usually gets what one deserves) and different kinds of causal attributions have on adjustment to sexual violence? Using a sample of N = 62 victims of sexual aggression (mean age = 21.7) it was shown that respondents were better able to adjust to their experience of sexual violence the higher their personal belief in a just world. Moreover, the more respondents attributed their victimization to situational circumstances (extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…Comer and Laird (1975) have shown experimentally that internal attributions seem to be a way of reevaluating one's fate as just. Although some research evidenced the hypothesized positive association between just world belief and internal attributions of the victims themselves (e.g., Hafer and Correy, 1999), other studies found no association between them (e.g., Fetchenhauer et al, 2005). People with a strong just world belief are expected to be motivated to defend their belief by making internal attributions of negative outcomes, thus maintaining their subjective well-being.…”
Section: Blaming the Victimmentioning
confidence: 99%
“…Comer and Laird (1975) have shown experimentally that internal attributions seem to be a way of reevaluating one's fate as just. Although some research evidenced the hypothesized positive association between just world belief and internal attributions of the victims themselves (e.g., Hafer and Correy, 1999), other studies found no association between them (e.g., Fetchenhauer et al, 2005). People with a strong just world belief are expected to be motivated to defend their belief by making internal attributions of negative outcomes, thus maintaining their subjective well-being.…”
Section: Blaming the Victimmentioning
confidence: 99%
“…Injustice is not expected in small-PD cultures (Gudykunst & Ting-Toomey, 1988;Matsumoto, 1989). For these reasons, people from small-PD cultures do not simply accept the status quo, but rather engage in more active communication, feeling more in control of their fate (Fetchenhauer, Jacobs, & Belschak, 2005).…”
Section: Power Distance and Injusticementioning
confidence: 99%
“…This belief was found to be a substantial personal resource in many domains, e.g. anger (Dalbert, 2002), sexual violence (Fetchenhauer, Jacobs, & Belschak, 2005), natural disasters (Otto, Boos, Dalbert, Schöps, & Hoyer, 2006), and stress (Otto & Schmidt, 2007), which in turn could imply that the personal resource function could also extend to economic events. Therefore, the present paper addresses the question of whether the belief in a just world may serve as a personal resource during adverse economic events.…”
Section: Introductionmentioning
confidence: 99%